A de novo partial trisomy 9p with Dandy-Walker malformation and ventriculomegaly - Che-Yen Kuan; Chi-Jung Tai; Ing-Luen Shyu; Yung-Chieh Tsai; Tian-Ni Kuo (Elsevier, 2022)
Objective: We present a female neonate with de novo trisomy 9p24.3-q21.2 presented with a neurological anomaly. Case report: Her birth length was 41 cm (<3rd percentile), birth body weight was 1600 g (<5th percentile), and head circumference was 29.5 cm (<5th percentile). She had low-set ears, deep and wide-set eyes with downslanting palpebral fissures, and a full nasal bridge with a globular nose. In addition, a rocker bottom foot was noted after further evaluation. Congenital heart anomalies, including patent ductus arteriosus (0.43 cm), large atrial septal defect, and malalignment ventricular septal defect (0.64 cm) were also confirmed. Brain magnetic resonance imaging showed partial agenesis of the cerebellum and corpus callosum. Furthermore, severe bilateral communicating hydrocephalus was found. CTG-banded chromosome analysis revealed 47, XX, +mar. Conclusion: DNA analysis may be mandatory for small gene segments. In trisomy 9p, we proposed further delineation of the critical region correlating to neurological malformations.